Clinical Features Assessment and Effect of Olfactory Training among COVID-19 Patients in the Kingdom of Saudi Arabia - Almutairi, Tahani Fahad; Al-Sowayan, Noorah Saleh (European Journal of Applied Sciences, 2022)
Coronavirus disease (COVID-19) was announced in Mar 2020 as a global pandemic. Olfactory dysfunction (OD) is a common consequence. Therefore, the present study assessed the prevalence of OD and other clinical features among COVID-19 patients in Saudi Arabia along with the effect of olfactory training. Eighty-two patients participated in this study and their demographics as well as clinical features, effect of olfactory training, and recovery time were assessed using a questionnaire. Patients with OD went through self olfactory training by sniffing essential oils twice a day for 30 or 40 sec, followed by 10 or 20 sec break then repeat for 5 or 10 min for 6 weeks. Our results revealed that 62% had OD in which 41% had hyposmia and 21% had anosmia, while 38% had normosia. Additionally, 80% lost their olfactory function during infection period, whereas 20% lost it post-infection. Most patients recovered their olfactory function after 2 weeks (39%). Moreover, 71% restored their olfactory function naturally, whilst 27% restored it by olfactory training, and 2% did not experience improvement. The frequently reported symptoms among OD patients included headache (62%), sore throat (60%), fever (54%), and cough (48%). Whereas the common symptoms among patients without OD are bone pain (38%), diarrhea (24%) anorexia (21%), and vomiting (11%). This study highlights the prevalence and underlying mechanism of OD and the potential effect of olfactory training using essential oils due to their unharmful bioactive molecules. The likely of OD makes it a recommended diagnostic tool in early COVID-19 stage.